THE EFFECT OF MATHEMATICAL DISPOSITION AND LEARNING MOTIVATION ON PROBLEM SOLVING: AN ANALYSIS - Masta Hutajulu; Tommy Tanu Wijaya; Wahyu Hidayat (Jurnal Infinity, 2019)
This research was motivated by the low problem solving abilities, mathematical disposition and learning motivation of junior students. This study aims to find and analyze empirically the influence of mathematical dispositions and learning motivation on problem solving abilities. Samples were obtained in class VII-2 at SMPN 2 Cimahi as many as 34 students.  Study uses correlational quantitative methods. Analysis was done by regression method. The data collection was given 2 pieces of study instruments, namely problem solving test instruments and non-test questionnaires in a set of mathematical dispositions and learning motivation. The data was tested for regression and correlation. The results of data analysis that was mathematical disposition and larning motivation were significantly influenced by problem solving ability of junior students, with the regression equation  indicating a positive influence, and the degree of closeness is the Pearson correlation coefficient of 0.827 classified in a strong positive interpretation. Together, mathematical disposition variables and learning motivation variables can determine the problem solving variable by 68.3%. Recommendations from this study, teachers should design learning processes that can improve mathematical disposition and student motivation so that students' problem solving abilities increase.